2022
DOI: 10.1097/jom.0000000000002587
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Stress, Depression, Quality of Life, and Intent to Leave in Washington State Emergency Medical Technicians During COVID-19

Abstract: Through a survey of emergency medical technicians in the Puget Sound region of Washington, we found that 67.5% of respondents reported high stress, and 35.0% had scores indicating that major depressive disorder was likely. Job demands were significantly associated with both stress and depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Consistent with the results found in our study, Srikanth et al 28 found that 23.8% of EMS providers were considering leaving the profession within 6 months. However, the study was only inclusive of a small sample from Puget Sound, Washington.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with the results found in our study, Srikanth et al 28 found that 23.8% of EMS providers were considering leaving the profession within 6 months. However, the study was only inclusive of a small sample from Puget Sound, Washington.…”
Section: Discussionsupporting
confidence: 93%
“…A web-based survey was developed in REDCap [ 36 ] to collect information on workplace experiences and concerns specific to mariners, mental health outcomes, and workplace factors such as safety climate and support. A working group consisting of University of Washington and NIOSH researchers as well as representatives from the external advisory group co-developed the survey, which was informed by mental health surveys deployed by investigators in other occupational cohorts during COVID-19 [ 30 , 32 ], as well as industry needs and previously validated scales.…”
Section: Methodsmentioning
confidence: 99%
“…Being mentally healthy is important for mariners given the mentally and physically demanding nature of their job, and the need to work as a cohesive crew. As poor mental health has been found to be related to injury at work [ 30 , 31 ], burnout [ 21 , 32 ], poor decision-making [ 33 ], and attrition [ 3 , 34 , 35 ] across a range of occupations, there is industry motivation to describe the burden of mental health outcomes of U.S. mariners and to develop interventions to improve mariner mental health, especially given the added changes and stressors faced by the industry due to COVID-19. Therefore, characterizing the mental health needs of mariners is of top priority for public health, and the maritime industry.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the stressors associated with this pandemic situation, many studies have shown a dramatic increase in turnover intention among physicians. [3][4][5][6][7] Turnover intention is the likelihood that employees will willingly leave their employment in the upcoming time and can be associated with two different intentions: internal and external. 8 External turnover (ET) consists of people leaving an organization, while internal turnover (IT) refers to transfers within the organization, such as asking to change departments.…”
mentioning
confidence: 99%
“…Physicians faced with this public health pandemic were put under physical and psychological stress and at high risk of infection and subsequent transmission to their family members. Because of the stressors associated with this pandemic situation, many studies have shown a dramatic increase in turnover intention among physicians 3–7 …”
mentioning
confidence: 99%